If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3e+3)=18
We move all terms to the left:
2(3e+3)-(18)=0
We multiply parentheses
6e+6-18=0
We add all the numbers together, and all the variables
6e-12=0
We move all terms containing e to the left, all other terms to the right
6e=12
e=12/6
e=2
| x+7/6=6 | | 5(g-2)=15 | | P×p=81 | | 2(f-2)=1 | | 5x–7=8x–13 | | 17i−4=200 | | 7m-2=1-3m | | 8y+2=-86 | | -x+17=-9 | | 5y+6=-54 | | 4(2z+1)=15 | | 2m-1=5m-3 | | (2x-15)+(x+5)+(3/2x-5)+(1/2x+15)=100 | | 4x=-5(1+3x)+5 | | 7e−3=25 | | 6(z+3)=30 | | 3(2a−5)=3+12a | | (2x-15)+(x+5)+(3/2x-5)+(12x+15)=100 | | 3x/4-12=1-x/3 | | 5/3x-1-7/6x=1/1-x | | 5x-18=15-6x | | a+4=a+18. | | 5(2g-4)=18 | | 5(3a-6)=15 | | 9+7x=100 | | 52=6+3+3+(x/4) | | x=-6=8 | | 4x-40=2(5x-4)-2 | | 10x+4=24+6x | | 2f/9-3=-2 | | 11x+22=7x+30 | | 11700=0,15x+0,24x |